Bernoulli inequality and hypergeometric functions - Riku Klén; Vesna Manojlović; Slavko Simić; Matti Vuorinen (AMER MATHEMATICAL SOC, 2022)
Bernoulli type inequalities for functions of logarithmic type are given. These functions include, in particular, Gaussian hypergeometric functions in the zero-balanced case F(a, b; a + b; x).